Enhanced Authentication by Virtual World (International Journal of Engineering and Computer Science, 2014)
Authentication is the process of verifying credentials of user and guarantees the user what it claims to be. Many ways of authentications are proposed starting from Textual Passwords, Graphical passwords, Biometrics etc. But all have certain limitations or drawbacks. Hence I propose a new way of Authentication which has capability of all existing authentication systems and is also suited for Client Server Architecture. This technique is based on real world simulation hence called Virtual World. User is given freedom to interact with virtual things and select his authentication mode i.e textual, graphical, Biometrics, OTP, Voice etc. This scheme provides more options and freedom to user along with have higher password space and hence difficult to break and thus more secured.